2017
DOI: 10.1038/s41598-017-07933-y
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Lysine-265 Allosterically Modulates Nucleotide- and Actin-binding Site Coupling in Myosin-2

Abstract: Myosin motor proteins convert chemical energy into force and movement through their interactions with nucleotide and filamentous actin (F-actin). The evolutionarily conserved lysine-265 (K265) of the myosin-2 motor from Dictyostelium discoideum (Dd) is proposed to be a key residue in an allosteric communication pathway that mediates actin-nucleotide coupling. To better understand the role of K265, point mutations were introduced within the Dd myosin-2 M765-2R framework, replacing this lysine with alanine (K265… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…Currently, no phenamacril-FgMyo1 structure derived from X-ray diffraction crystallography is available to aid the interpretation of our findings. From one perspective, residues such as K216 in FgMyo1 (one of the amino acids associated with resistance) is known to constitute part of an allosteric communication pathway which transmits information between the nucleotide-and the actin-binding site [19,20,29,39]. These mechano-chemical events involve larger structural changes such as cleft-opening or closure and rotation of the lever arm.…”
Section: Resistant Fusarium Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, no phenamacril-FgMyo1 structure derived from X-ray diffraction crystallography is available to aid the interpretation of our findings. From one perspective, residues such as K216 in FgMyo1 (one of the amino acids associated with resistance) is known to constitute part of an allosteric communication pathway which transmits information between the nucleotide-and the actin-binding site [19,20,29,39]. These mechano-chemical events involve larger structural changes such as cleft-opening or closure and rotation of the lever arm.…”
Section: Resistant Fusarium Strainsmentioning
confidence: 99%
“…This could potentially affect more distal binding-sites. From another perspective, the actin-binding cleft is also known to harbor allosteric binding sites [18][19][20][21]24] and the halogenated pseudilins mediate their inhibitory effect through direct interactions with a conserved lysine residue (K216 in F. graminearum) [19,20,29,39]. This therefore speaks for a binding of phenamacril in the vicinity of the residues associated with resistance.…”
Section: Resistant Fusarium Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance development was observed to correlate with amino acid mutations, which are primarily located within the actin-binding cleft of the myosin motor domain (4,5,19). This region is known to play a pivotal role in mediating allosteric communication between the nucleotide-and actin-binding sites (21)(22)(23). It is a well-characterized and conserved allosteric site targeted by other classspecific myosin inhibitors such as blebbistatin (24) and the halogenated pseudilins (21,23,25).…”
mentioning
confidence: 99%
“…Pivotal to this allosteric communication is the central seven-stranded β-sheet (the transducer) (twisted in the rigor state, but untwisted in the pre-power stroke state) in the myosin motor domain, which couples the large actin-binding cleft (closed while strongly attached to F-actin, and open in actin-detached states) with the active site phosphate-sensing elements—the P-loop, switch-1 and switch-2—(closed in the hydrolysis-competent pre-power stroke state, but partially or fully opened in all other states) as well as through the relay helix (bent in the pre-power stroke state, while straight in the rigor state) and SH1/SH2-region with the mechanical converter and lever arm (down position in the rigor state, and up position in the pre-power stroke state). We and others have shown that mutations in these key regions disturb the motor function by interfering with chemomechanical coupling pathways [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%